Protein and Amino Acid Nutrition of Marine Fish Species - Peres, Helena; Oliva-Teles, Aires (Avances en Nutrición Acuicola, 2017)
Intensive aquaculture of marine fish species has highly expanded during the last decades and has potential for further increase. An increased and consistent supply of high quality aquafeed will be required to sustain this production and to guaranty the production of protein of high biological value for humans. Protein is the most abundant and expensive dietary nutrient in aquafeeds and fish meal is still the major dietary protein source in marine aquafeeds. Given the zootechnical, environmental and economical importance of a well-balanced diet, fine-tuning of dietary protein and amino acid composition to closely meet fish requirements are therefore of utmost importance. This is of particular importance when it is considered the dietary replacement of fish meal by more sustainable and renewable protein sources, such as plant feedstuffs, which have amino acids unbalances, antinutritional factors, lower protein content and digestibility, and devoid or containing very low concentrations of some particular micronutrients, as taurine. Concomitantly, in fish the utilization of amino acids for energy purpose is considered high, and so optimization of amino acids/protein accretion has great importance and practical implications. Besides the nutritional proprieties of amino acids, emerging evidence shows that some of them have functional properties, regulating key metabolic pathways crucial to maintenance, growth, and immune responses, being of strong interest in fish production. The importance of gaining further knowledge regarding amino acid requirements, metabolism and utilization as functional ingredients in aquaculture fish species will be stressed.